Embryology of Ageratum conyzoides L. and A. fastigiatum R.M. King & H. Rob. (Asteraceae) - Franca,Rafael de Oliveira (2015)
Ageratum has a complex circumscription, and recent studies have indicated its polyphyletism. The genus has been placed in the tribe Eupatorieae whose embryology is not fully known. Embryological data are conservative and important indicators of phylogenetic relationships and can improve family relationships. This study presents, for the first time in Eupatorieae, embryological data for Ageratum conyzoides and A. fastigiatum. Both species have common features of the family such as a unitegmic anatropous ovule, basal placentation, secretory tapetum, Polygonum megagametophyte, and Asterad embryogenesis. The data obtained reinforce the heterogeneity of the family embryology and show, for the first time, the anther wall development of the monocotyledonous type for Asteraceae. The species studied show also differences between themselves. A. conyzoides has bisporangiated and introrse anthers, conspicuous pappus, and cypselae with trichomes on the ribs, whereas A. fastigiatum has tetrasporangiate and latrorse anthers, pappus absent at maturity, and glabrous cypselae. The data presented support recent phylogenetic molecular studies, suggesting the replacement of A. fastigiatum to another genus along with Gyptidinae.